Predictive classification of attentional profiles at age 3-years from early development using a machine learning approach - Musso, Mariel Fernanda (2023)
This study presents four attentional profiles in early development using a novel attention task. This study also aims to develop machine learning models to classify children into these profiles from a broad range of data acquired in infancy. A total of 76 toddlers participated as part of a longitudinal project.